2017
DOI: 10.1002/mus.25707
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of rat muscle size but not function more than 1 year after a single botulinum toxin injection

Abstract: The data demonstrate that, after a single BT-A injection, although gross muscle morphology recovered over a 12-month time period, loss of contractile function did not recover. Muscle Nerve 57: 435-441, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 32 publications
5
50
0
Order By: Relevance
“…This study has found that, at 25 weeks, muscle volume has not fully recovered, consistent with previous animal 9,27 and human research. 11 Previously published data by Barber et al 15 found that, at 52 weeks, injected gastrocnemius showed a 4.8% increase in normalized volume (calculated on the basis of presented fibula lengths) in toxin-naive children with CP.…”
Section: Discussionsupporting
confidence: 91%
“…This study has found that, at 25 weeks, muscle volume has not fully recovered, consistent with previous animal 9,27 and human research. 11 Previously published data by Barber et al 15 found that, at 52 weeks, injected gastrocnemius showed a 4.8% increase in normalized volume (calculated on the basis of presented fibula lengths) in toxin-naive children with CP.…”
Section: Discussionsupporting
confidence: 91%
“…Thirty 300 g male Lewis rats underwent survival surgery under isoflurane anaesthesia with analgesia provided with preoperative subcutaneous injection of 0.3 mg sustained release buprenorphine (Buprenorphine SR-LAB, ZooPharm, Windsor, Colorado, USA). Common peroneal (fibular) nerves were exposed bilaterally at the proximal lateral margin of the knee joint using a technique previously described 22 23. The fascial sheath overlying the nerve was left intact.…”
Section: Methodsmentioning
confidence: 99%
“…End points were assessed at 3, 14, 30, 90, and 180 days following treatment, a time frame over 3x longer than that during which a small population of persistent motor deficits were observed 2323.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Muscle & Nerve, you will find an interesting study entitled "Recovery of Rat Muscle Size but Not Function More Than 1 Year After a Single Botulinum Toxin Injection" by Ward et al 3 In their study, adolescent rats received a single botulinum toxin injection, and muscle anatomy and function were then assessed throughout an 18month period and compared with a saline-injected cohort. A surprising finding was that, 1 year later, after toxin injection, dorsiflexion torque production remained depressed by 25% compared with the contralateral leg, whereas gross morphology had recovered.…”
mentioning
confidence: 99%